Left ventricular morphology in junior and master resistance trained athletes - Haykowsky, M. J.; Quinney, H. A.; Gillis, R.; Thompson, C. R. (Medicine & Science in Sports & Exercise, 2000)
Purpose: The objective of this cross-sectional investigation was to assess the effects of short (<5 yr) versus long-term (>18 yr) resistance training (RT) on left ventricular (LV) dimensions and mass. Methods: The subjects for this study were 20 elite male powerlifters (8 junior athletes [JA], mean ± SD, age: 21.1 ± 1.2 yr and 12 master athletes [MA], age: 46.0 ± 5.5 yr) and 19 age-matched male controls (8 young controls [YC], age: 21.8 ± 2.8 yr and 11 middle-aged controls [MAC], age: 46.8 ± 4.4 yr). Two-dimensionally guided transthoracic M-mode echocardiograms were performed at rest to quantify LV systolic and diastolic cavity dimension (LVIDs and LVIDd, respectively), ventricular septal wall thickness (VST), posterior wall thickness (PWT), LV mass (LVM), and LV systolic function as measured as fractional shortening (FS). Results: Short- or long-term RT was not associated with a significant alteration in LVIDd (JA: 53.2 ± 4.5 mm, YC: 52.1 ± 3.7 mm, MA: 53.0 ± 5.1 mm, MAC: 51.8 ± 4.4 mm), LVIDs (JA: 33.5 ± 4.8 mm, YC: 32.9 ± 3.4 mm, MA: 33.0 ± 4.4 mm, MAC: 31.4 ± 3.7 mm), VST (JA: 9.4 ± 0.9 mm, YC: 9.4 ± 0.9 mm, MA: 9.4 ± 1.6 mm, MAC: 9.7 ± 0.9 mm), PWT (JA: 9.2 ± 0.9 mm, YC: 9.4 ± 0.9 mm, MA: 9.0 ± 1.1 mm, MAC: 9.5 ± 1.0 mm), LVM (JA: 184.6 ± 36.1 g, YC: 179.0 ± 26.5 g, MA, 183.3 ± 58.1 g, MAC: 184.1 ± 38.1 g), or FS (JA: 0.37 ± 0.1%, YC: 0.37 ± 0.05%, MA: 0.38 ± 0.1%, MAC: 0.40 ± 0.04%). Conclusions: These findings suggest that short or long-term RT as performed by elite junior and master powerlifters does not alter LV morphology or systolic function.